Distinguishing Sepsis From Infection by Neutrophil Dysfunction: A Promising Role of CXCR2 Surface Level - Seree-aphinan, Chutima; Vichitkunakorn, Polathep; Navakanitworakul, Raphatphorn; Khwannimit, Bodin (Frontiers in Immunology, 2020)
Sepsis is one of the well-established diseases with specific patterns of neutrophil dysfunctions. Previous studies demonstrated sepsis-related neutrophil dysfunctions in comparison with subjects without infection. Since sepsis and infection are recently recognized as distinctive processes, whether these neutrophil dysfunctions are associated with sepsis or infection are not known. Therefore, we longitudinally compared neutrophil functions, widely-cited as exhibiting sepsis-related changes, between patients with septic shock and infection. The surface level of cluster of differentiation 64 (CD64), C-C motif chemokine receptor 2 (CCR2), C-X-C motif chemokine receptor 2 (CXCR2); apoptosis; and NETosis, were measured from peripheral blood neutrophils for seven consecutive days using flow cytometry. The between-group comparisons of neutrophil functions were made both on a day-by-day basis and as linear regression between time and measured neutrophil functions (sepsis status included as model predictors). Our study found that, among neutrophil functions studied, only CXCR2 surface level is associated with sepsis. At disease onset, CXCR2 level decrease; with a dose-response relationship with clinical severity. Its level reverts to resemble infected patients by the end of the week. The relationship between CD64 surface level, CCR2 surface level, NETosis, and sepsis are mediated through the effect of infection. Apoptosis activity between these groups are similar, hence, not sepsis-related.